Tissue polarity genes of Drosophila regulate the subcellular location for prehair initiation in pupal wing cells. - Wong, L.L.; Adler, P.N. (Journal of Cell Biology, 1993)
The Drosophila wing is decorated with a regular array of distally pointing hairs. In the pupal wing, the hairs are formed from micro-villus like prehairs that contain large bundles of actin filaments. The distal orientation of the actin bundles reveals the proximal-distal polarity within the pupal wing epithelium. We have used F-actin staining to examine early stages of prehair development in both wild-type and mutant pupal wings. We have found a striking correlation between hair polarity and the subcellular location for assembly of the prehair. In a wild-type wing, all of the distally pointing hairs are derived from prehairs that are formed at the distal vertex of the hexagonally shaped pupal wing cells. Mutations in six tissue polarity genes result in abnormal hair polarity on the adult wing, and all also alter the subcellular location for prehair initiation. Based on their cellular phenotypes, we can place these six genes into three phenotypic groups. Double mutant analysis indicates that these phenotypic groups correspond to epistasis groups. This suggests that the tissue polarity genes function in or on a pathway that controls hair polarity by regulating the subcellular location for prehair formation.